1997
DOI: 10.1007/pl00005093
|View full text |Cite
|
Sign up to set email alerts
|

Cannabinoid CB1 receptor-mediated inhibition of noradrenaline release in the human and guinea-pig hippocampus

Abstract: We examined the question of whether cannabinoid receptors modulating noradrenaline release are detectable in the brain of humans and experimental animals. For this purpose, hippocampal slices from humans, guinea-pigs, rats and mice and cerebellar, cerebrocortical and hypothalamic slices from guinea-pigs were incubated with [3H]noradrenaline and then superfused. Tritium overflow was evoked either electrically (0.3 or 1 Hz) or by introduction of Ca2+ ions (1.3 mM) [corrected] into Ca(2+)-free, K(+)-rich medium (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
76
1
2

Year Published

1999
1999
2013
2013

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 134 publications
(84 citation statements)
references
References 21 publications
5
76
1
2
Order By: Relevance
“…The primary pharmacological property of desipramine is its ability to inhibit norepinephrine reuptake and thus potentiate the synaptic action of norepinephrine (Frazer, 1997;Wong et al, 2000). Both in vivo and ex vivo work in rodent and human tissue has demonstrated that CB 1 receptors in the hippocampus and hypothalamus negatively regulate noradrenergic neurotransmission (Tzavara et al, 2001;Schlicker et al, 1997). Thus, the upregulation of CB 1 receptors in the hippocampus and hypothalamus seen in this study could be an adaptive response launched by the central nervous system to decrease noradrenergic transmission by increasing the density of presynaptic CB 1 receptors, which in turn would reduce NE release and normalize the increased synaptic availability induced by desipramine treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The primary pharmacological property of desipramine is its ability to inhibit norepinephrine reuptake and thus potentiate the synaptic action of norepinephrine (Frazer, 1997;Wong et al, 2000). Both in vivo and ex vivo work in rodent and human tissue has demonstrated that CB 1 receptors in the hippocampus and hypothalamus negatively regulate noradrenergic neurotransmission (Tzavara et al, 2001;Schlicker et al, 1997). Thus, the upregulation of CB 1 receptors in the hippocampus and hypothalamus seen in this study could be an adaptive response launched by the central nervous system to decrease noradrenergic transmission by increasing the density of presynaptic CB 1 receptors, which in turn would reduce NE release and normalize the increased synaptic availability induced by desipramine treatment.…”
Section: Discussionmentioning
confidence: 99%
“…*P<0.05, compared with the corresponding control (not shown). From Kathmann et al (2001a), Kurz et al (2008), Nakazi et al (2000), Schlicker et al (1996Schlicker et al ( , 1997Schlicker et al ( , 2003, Schultheiss et al (2005) and unpublished data brain regions of the guinea pig (Kathmann et al 1999;Schlicker et al 1997). A facilitating effect of rimonabant was also found in the rat medial prefrontal cortex and nucleus accumbens (Tzavara et al 2003).…”
Section: Effects On Transmitter Releasementioning
confidence: 93%
“…Antagonism of inhibition of cAMP formation has also been observed in peripheral tissues such as the rat vas deferens (Pertwee et al 1996c) or the trabecular meshwork and ciliary process of the human eye (Stamer et al 2001). Whereas some studies report that rimonabant does not affect intracellular cAMP levels in the absence of exogenous cannabinoids (Rinaldi-Carmona et al 1994;Schlicker et al 1997), others have found cAMP elevations upon in vitro or in vivo treatment with rimonabant (Mato et al 2002;Rubino et al 2000). Interestingly, rimonabant treatment was also found to activate protein kinase A (Rubino et al 2000;Tzavara et al 2000).…”
Section: Cellular Effectsmentioning
confidence: 99%
See 2 more Smart Citations